Prevalence and Associated Factors of Frailty in Community-Dwelling Older Adults in Indonesia, 2014-2015 - Supa Pengpid (2020)
Objective: The investigation aims to study the prevalence and correlates of frailty in a national community-dwelling sample of older Indonesians. Methods: Participants were 2630 older adults, 60 years and older (median age 66.0 years, interquartile range = 9.0) who took part in the cross-sectional Indonesia Family Life Survey (IFLS-5) in 2014-2015. They were requested to provide information about sociodemographic and various health variables, including frailty. Multivariable Poisson regression analysis was utilized to estimate the correlates of socio-demographic factors, health variables, and frailty. Results: The overall prevalence of frailty was 8.1%; 61.6% were prefrail. In adjusted Poisson regression analysis, older age, being unmarried, separated, divorced or widowed, residing in Java and major island groups, poor cognitive functioning, loneliness, and functional disability were associated with frailty. Conclusion: Several sociodemographic and health risk factors for frailty were identified that can help in guiding intervention strategies in Indonesia.